Prevalence of overweight and obesity in Iranian population: A population-based study in northwestern of Iran - Farhad Pourfarzi; Alireza Sadjadi; Hossein Poustchi; Firouz Amani (SAGE Publishing, 2021)
Background: Overweight and obesity and its problems are the most important health and nutrition issues of adolescents in developed and developing countries. This study aimed to determine prevalence of overweight and obesity among studied population. Design and Methods: This Persian Cohort Study is a population-based study of 10,000 men and women, aged 35-70 years in northwest of Iran. Anthropometric parameters such as height, weight, waist circumference and hip circumference were measured by interviewers. Body Mass Index (BMI) and waist-to-hip ratio (WHR) were used to assess the overweight and obesity. Results: The mean age of all participants was 49.1±8.7 and 56.1% of them were female.  The mean height of participants was 162.5±9.4 kg in range 126-196 and the mean weight of them was 78.5±13.1 cm in range 40-164. According to BMI, 42.7% of all participants had overweight and 45% had obesity. According to the WHR, 71.8% of male and 97.9% of female had high WHR (abdominal obesity). Conclusions: Results showed that the rate of overweight and obesity in studied people was more than country rate. So programing for raising their Quality of Life (QoL) and life style and also change their poor nutritional habits is essential in area healthy people.